Evaluation of the Teaching-Learning Process of Gas Turbine Engine Fundamental Using Generic Features of Good Teaching - Widoro, Ego; Situmorang, Robinson; Anis Chaeruman, Uwes (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
Understanding gas turbine engines as aircraft propulsion engines is essential in aircraft maintenance. It was found that the learning outcomes for basic turbine motor courses (gas turbine engine fundamentals) were not optimal. This research aims to learn and teach basic motorbike courses that focus on finding out learning activities based on the general features of good teaching Gall et al. (2007) in the basic course on turbine motors at the TPU D.IV Study Program. This research was conducted in June-July 2022 and used qualitative methods with semi-structured interviews, observations, and theoretical studies to collect qualitative data. Six findings, namely lack of student involvement; activity plans inside and outside lectures are inadequate; need to maintain and plan better practical activities; no program for implementing understanding in the classroom; and emphasis on activities in pairs or groups. The limitation of this research is that it only examines teaching and learning activities. There may be other parameters that can influence academic achievements such as student characteristics, availability of learning materials, facilities, etc., or developing learning with a structured active learning approach to maintain student involvement and understanding of the content that needs to be carried out in further research.